Pólipos endometriais na pós-menopausa: Aspectos clínicos, epidemiológicos e pesquisa do polimorfismo do receptor da progesterona (PROGINS) - Miranda, Simone Madeira Nunes [UNIFESP] (2009)
Purpose: To evaluate the genetic polymorphism of the progesterone receptor (PROGINS), as well as clinical and epidemiological risk factors for endometrial cancer in postmenopausal women with endometrial polyps. Methods: A case control study was designed with 154 postmenopausal women with endometrial polyps, compared to a normal control group of 400 postmenopausal women. The genotyping of PROGINS polymorphism was determined by polymerase chain reaction. The group of polyps was compared to 118 normal postmenopausal controls regarding clinical and epidemiological variables. These variables were also compared between benign and malignant endometrial polyps. Results: The epidemiological variables among the group of endometrial polyps and normal control, showed statistical significance (p<0,05) for age: media of 61,7 and 57,5 years, ethnicity non-white 44,8% and 22,9%, time since menopause media of 12,9 and 9,2 years, parity media of 4,5 and 3,4 sons, tamoxifen use 5,2% and 0%, hypertension 54,5% and 29,7% and history of breast cancer 10,4% and 0,8% respectively. After age adjust, statistical significance, remained only for parity (OR=1,13), hypertension (OR=2,19) and history of breast cancer (OR=14,44). Postmenopausal bleeding and large polyps were present in all cases of malignancy. Hypertension was also very frequent in malignant polyps (83,3% and 54,5% respectively). The presence of PROGINS had no statistical significance between the group of polyps and the normal control (N=400). The presence of wild homozygosis genotype, heterozygosis and mutant homozygosis was 79,9%, 19,5% and 0,6% respectively for the polyp group, and 78,8%, 20,8% and 0,5% for the control group (p=0,208). Conclusions: There was no significant association between the presence of PROGINS and endometrial polyps. After age adjust, epidemiological variables significantly associated to endometrial polyps were elderly age, parity, hypertension, and history of breast cancer (implicit tamoxifen use). Malignant polyps in this study were always associated to postmenopausal bleeding, large polyps and frequently associated to hypertension.